OCCUPATION MILITAIRE ET DÉSENGAGEMENT DE L’OUGANDA DE LA RÉPUBLIQUE DÉMOCRATIQUE DU CONGO : Enjeux et implications dans les conflits armés en Ituri. - Agenonga Chober ,; Bahinduka Besisa, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The violent armed conflicts that had shaken the former Congolese district of the Ituri go back up in 1999, period marked by the military occupation of a part of the territory of the Democratic Republic of Congo (DRC) by the Ugandan troops. At the end of an agreement of disengagement signed in Luanda (Angola) in 2002 by Kampala and Kinshasa, the Ugandan troops accused rightly or wrongly of these conflicts, retired of the Congolese soil, an event that, theoretically, should sign the end of the war previously in this country and the restoration of the authority of the state in the zones under the rebel control, in this case the Ituri. This note of analysis uses itself to diagnose the impact of the withdrawal of these troops on the conflicts that put to the holds the Hema communities and Lendus. In an approach geopolitics, this analysis puts in light the implications and the stakes of this withdrawal in the persistence or in the stop of the violence. And that, in order to clarify the means whose actors arranged, their operative fashion as well as the alliances and/or outside complicities of which they benefitted.